Assessment and improvement of junior doctor handover in the emergency department. Issue 3 (18th August 2020) - Sykes, Mark; Garnham, Jack; Kostelec, Pablo Martin; Hall, Hazel; Mitra, Anu
Abstract : Introduction: Effective handover between junior doctors is widely accepted as essential for patient safety. The British Medical Association in association with the National Health Service (NHS) National Patient Safety Agency and NHS Modernisation Agency have produced clear guidance regarding the contents and setting for a safe and efficient handover. We aimed to understand current junior doctor's opinions on the handover process in a London emergency department (ED), with subsequent assessment, and any necessary improvement, of handover practices within the department. Methods: In a London ED, a baseline survey was completed by the senior house officer (SHO) cohort to gauge current opinions of the existing handover process. Concurrently, a blinded prospective audit of handover practises was conducted. Multiple improvement strategies were subsequently implemented and assessed via Plan–Do–Study–Act (PDSA) cycles. A standard operating procedure was initially introduced and 'rolled out' throughout the department. This intervention was followed by development of an electronic handover note to ease completion of a satisfactory handover. Additional surveys were conducted to continually assess SHO opinion on how the handover process was developing. The final improvement strategy was formal handover teaching at the SHO induction. Results: Baseline audit and SHO survey highlighted several opportunities for improvement. 5 handover components were deemed essential: (1) documented handover note; (2) doctor's names; (3) history of presenting complaint; (4) ED actions; and (5) ongoing plan. The frequency of these components saw significant improvement by completion of the final PDSA. Following SHO rotation, all of the essential components fell, only to recover after the next improvement strategy. Conclusions: Junior doctors in a London ED were not satisfied with the current SHO handover process, and handover practices were not adequate. While the rotational nature of the SHO cohort makes sustained change challenging, implementation of thoughtful and realistic improvement strategies can significantly improve handover quality.